Career theory and practice : learning through case studies - Swanson, Jane Laurel; Fouad, Nadya A. (Thousand Oaks, California : SAGE Publications, 2019)
"Career Theory and Practice: Learning Through Case Studies is designed to illustrate the process, theories, and application of career development counseling through a series of rich case studies. Authors Jane L. Swanson and Nadya A. Fouad use this approach throughout the book to highlight the similarities and differences between the featured theories, as well as to illustrate proper technique and application. The fully revised Fourth Edition features expanded coverage of testing and assessments, issues related to intersectionality, new chapters on the Psychology of Working, Social Constructionism, combining approaches from multiple theoretical perspectives, Ethical and Professional Issues, and Integrating Career Development in Different Settings, and an increased focus on substance use and mental health disorders"--
Includes bibliographical references (pages 264-279) and index.
English.
Keywords: Career development -- Case studies; Vocational guidance -- Case studies